Pesticide, Performance, Protest: The Theatricality of Flesh in Nicaragua - Guevara, Alberto (InTensions, 2008)
This paper explores affliction in the intersection between the human body, social violence and theatricality. It argues that in Nicaragua, ‘victims’ of pesticide contamination wield their suffering flesh as theatrical weapons. Banned in the USA as early as the 1970s, but used since in banana plantations by multinational companies in many developing nations, the pesticide nemagón has become the perfect metaphor for evoking structural violence in Nicaragua today. As a result of contact with the pesticide at least one thousand Nicaraguans have died to date. For several years now thousands of men and women, together with their families, have staged a number of public protests. Partaking in long highway marches of up to 140 kilometers from their communities in Northwestern Nicaragua to the capital Managua, setting up tent cities and performing other well-known spectacular protests, they have called attention to their social situation.